TECHNICAL EFFICIENCY OF TILAPIA PRODUCTION IN ILHA SOLTEIRA, SP: A NONPARAMETRIC ANALYSIS - Sabbag, Omar Jorge [UNESP]; Almeida Lima Costa, Silvia Maria [UNESP] (Inst Zootecnia, 2015)
The objective of this study was to analyze the performance of tilapia production units using tank networks for fish production in the Ilha Solteira reservoir, SP. The degree of productive efficiency and the differential of each raw material to achieve efficiency of the production systems in tank networks were evaluated. Methodologically, input-oriented data envelopment analysis (DEA) under constant returns to scale was applied. The variables analyzed were investments, effective operational costs, investment compensation (inputs), and production (output). The results showed that 25% of the units were very efficient, with average investments of R$241,000.00, operational costs of R$86,000.00, and production corresponding to 23 tons/month. The results point to the recommendation that the production unit (DMU) with low performance reduces the use of inputs by 53% to become efficient. Fish farmers should pay more attention to actions that do not contribute to the optimization of available infrastructure, especially investments, the factor responsible for the greater degree of inefficiency in the DMU analyzed.
Keywords: DEA; performance; management; fish farming